2020
DOI: 10.1039/d0fo01954b
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of non-alcoholic fatty liver disease by sodium butyrate is linked to the modulation of intestinal tight junctions in db/db mice

Abstract: Intestinal microenvironment, a potential factor that contributed to the development of non-alcoholic fatty liver disease (NALFD) and type 2 diabetes (T2DM), have a closely relationship with intestinal tight junctions (TJs)....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 69 publications
0
57
0
Order By: Relevance
“…However, the levels of SCFAs were not dramatically different from that in the mice with SB intake. For the first time, we found that supplementation with SB had a limited effect on the level of SCFAs in mice infected with H. pylori , and this limited effect may be related to the limited effect of SB on the metabolites of the gut microbiota, the composition of the gut microbiota, the dose of SB or the absorption of SB in the gastrointestinal tract 45‐50 . Thus, further studies should be conducted to evaluate potential mechanistic relationships between gut microbiota and SCFAs in the future.…”
Section: Discussionmentioning
confidence: 85%
“…However, the levels of SCFAs were not dramatically different from that in the mice with SB intake. For the first time, we found that supplementation with SB had a limited effect on the level of SCFAs in mice infected with H. pylori , and this limited effect may be related to the limited effect of SB on the metabolites of the gut microbiota, the composition of the gut microbiota, the dose of SB or the absorption of SB in the gastrointestinal tract 45‐50 . Thus, further studies should be conducted to evaluate potential mechanistic relationships between gut microbiota and SCFAs in the future.…”
Section: Discussionmentioning
confidence: 85%
“…The decreased lipid storage in the liver upon butyrate exposure could be due to increased lipolysis in hepatocytes themselves and other cells such as adipocytes [44][45][46][47], but possibly also because of increased lipid storage in other organs, such as the muscle [45] or even intestine. Nonetheless, it is unclear whether butyrate can induce lipid storage in vivo in the colon, and how the nutritional environment affects the outcome of butyrate exposure in the colon.…”
Section: Discussionmentioning
confidence: 99%
“…24 As in previous studies, LPS treatment resulted in histopathological lesions, including inflammatory infiltrates, mucosal and crypt lesions, and epithelial changes. 25 In epithelial and immune cells, TLRs play a role in the body's immune system as pattern recognition receptors. TLR4, a member of the toll-like receptor family, can recognize the LPS produced by Gram-negative bacteria and activate NF-κB and mitogen-activated protein (MAPK), two classical inflammatory response pathways, and lead to an increase in inflammatory cytokines (TNF-α, IL-6, IL-1β, etc .).…”
Section: Discussionmentioning
confidence: 99%